Set-Membership Orthogonal Gradient Adaptive Algorithm on Least Mean Fourth Criterion - Suchada Sitjongsataporn; Theerayod Wiangtong; P. Pookaiyaudom (My University, 2024)
In this paper, we introduce a set-membership mechanism on the orthogonal gradient adaptive (OGA) algorithm based on least mean fourth (LMF) algorithm. In accordance with the fast convergence, the OG A-based scheme is conducted based on LMF algorithm that is described with the fourth power of the estimated error. The organisation of proposed algorithm composes with a brief of set-membership adaptive filtering and taking an advantage of OGA algorithm based on LMF algorithm. In order to make a smooth, an adaptive learning rate of algorithm and threshold value are furnished for convergence rate performance. There are some experimental simulations from proposed algorithm that show the mean square error trends can converge remarkably to the existing algorithm for system identification.
Keywords: Advanced Adaptive Filtering Techniques